Valorization of Cherry Waste in Edible Films: Effects of Glycerol on Stability and Antioxidant Activity - Matiacevich, S (SPRINGER, 2025)
Sustainable food industry seeks natural antioxidants from agro-industrial wastes. Stability of freeze-dried sweet-cherry powder (CP), alone or loaded in low-methylesterified pectin films, non-plasticized (NPF) or glycerol plasticized (PF), was studied at 25 degrees C under controlled relative humidity (RH). Phenolics composition and antioxidant capacity under accelerated oxidation (RapidOxy) were evaluated. CP at 0%-RH preserved its antioxidant capacity for 441 days. Meanwhile, the antioxidant activity decreased in NPF and PF at 75.2%-RH. Anthocyanins and flavonols were preserved for 83 days at 0%-RH in CP and NPF, maintaining red color. CP in brittle NPF (0%-RH) allowed its use as a milled stabilized food powder. Under accelerated oxidation, anthocyanins were the most degraded, while hydroxycinnamic acids remained stable. Glycerol increased films oxidative stability. At 75.2%-RH, phenolics were best preserved from oxidation in NPFs for 441 days. These findings aid in preserving natural antioxidants and developing edible active films offering natural coloring for sustainable food industries.
Keywords: Agroindustrial wastes; Sweet cherry powder; Antioxidant functional edible films; Phenolic compounds; Oxidation stability